Know-hows of Zero Tillage Technology and the Associated Constraints Experienced by the Farmers in Rice-Wheat Cropping System of Eastern Uttar Pradesh - Kumari, Anuradha Ranjan; Dubey, S. K.; Pundir, Ajay; Gautam, U.S. (Indian Journal of Extension Education, 2018)
The study was conducted in Deoria district of eastern Uttar Pradesh as the part of CIMMYT-CSISAproject. Out of sixteen  blocks three blocks i.e. Bhatni, Bankata and Pathardewa were selected for this study as the project was implemented in  these blocks. From each blockthree villages were selected purposively. From these villages fifteenzero tillage practicing  farmers were selected. Hence total sample size was 135 farmers. The data were collected from through personal interview  method with the help of structured interview schedule. The knowledge and constraints in practicing zero tillage  technology were analyzed. The findings revealed thatmost of the farmers had knowledge about the practices of zerotillage  technology. Majority of the respondents are agreed that saving of cost to the extent of 1500/acre (97.03%), need of post emergence herbicides application as necessary in zero tillage (94.81%), suitable for low lying areas (93.33%), saves water  in first irrigation (92.59%) and phosphorus is placed at right depth in soil with zero till (91.85%)were the effect of the  zerotillage technology. The findings also revealed that loose straw management is problem and lack of local mechanic to  repair the machine was the major technical constraints faced by majority of respondents. Less coverage of mass media and  lack of training on zero tillage technology to meet the information needs were observed as the most serious training and  educational constraints. Higher cost of zero till machine (70.37%), lack of cooperation among farmers to share experience  (67.40%) and lack of knowledge of farmers about minor adjustments of machine (80.74%) were reported as major  constraints under financial, socio-psychological and extension constraints respectively.
Keywords: Constraints; cropping system; effect; rice-wheat; zero tillage technology